1990
DOI: 10.1128/aac.34.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-binding protein 3 of Listeria monocytogenes as the primary lethal target for beta-lactams

Abstract: Penicillin-binding proteins (PBPs) of Listeria monocytogenes were detected by their ability to bind to [2,3-3H]benzylpenicillin. Five proteins with M,s of 95,000, 84,000, 80,000, 76,000, and 49,000 were detected. PBPs 1 to 4 had a high affinity for [2,3-3H]benzylpenicillin and were relatively scarce (80 to 150 molecules per cell). In contrast, PBP 5 was more abundant (600 molecules per cell) but had a low affinity for [2,3-3Hlbenzylpenicillin. L. monocytogenes has a relatively high natural resistance to cephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 5 publications
1
63
0
2
Order By: Relevance
“…The sensitivity of L. monocytogenes EGD/⌬lmo2229 to ␤-lactams and vancomycin was similar to that of the wild type. The results show that PBP4 does not contribute to the natural resistance of L. monocytogenes to cephalosporins and monobactams, which is due to the low affinity of PBP3 and PBP5 for those antibiotics (24,34). Similarly, inactivation of lmo2229 had no effect on the sensitivity of the L. monocytogenes EGD/⌬lmo2229 mutant to nisin compared to the wild type; a slight increase in nisin sensitivity was previously reported in L. monocytogenes strain 412 upon lmo2229 disruption (12).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The sensitivity of L. monocytogenes EGD/⌬lmo2229 to ␤-lactams and vancomycin was similar to that of the wild type. The results show that PBP4 does not contribute to the natural resistance of L. monocytogenes to cephalosporins and monobactams, which is due to the low affinity of PBP3 and PBP5 for those antibiotics (24,34). Similarly, inactivation of lmo2229 had no effect on the sensitivity of the L. monocytogenes EGD/⌬lmo2229 mutant to nisin compared to the wild type; a slight increase in nisin sensitivity was previously reported in L. monocytogenes strain 412 upon lmo2229 disruption (12).…”
Section: Discussionmentioning
confidence: 57%
“…PBP3 was proposed to be the lethal target for ␤-lactams in L. monocytogenes (34), whereas increased expression of PBP4 together with a histidine kinase was associated with resistance to nisin (12,13), an antibacterial peptide which exerts its action by forming pores in the cytoplasmic membrane through interaction with the PG precursor lipid II (4). Although hundreds of proteins with GT-TP architecture have been identified, very few of them have been isolated and only a few of their properties have been characterized so far (3,8,28,30).…”
mentioning
confidence: 99%
“…A first study reported that L. monocytogenes had five PBPs, as detected by their ability to bind benzylpenicillin (186). By searching the genome, Guinane and colleagues recently found seven surface proteins with similarities to PBPs (71).…”
Section: Cell Wall Metabolismmentioning
confidence: 99%
“…PBPD1 (formerly VOL. 71,2007 LISTERIA SURFACE PROTEINS 387 PBP5 [186]) and PBPD2 are related to the peptidase S11 family (Pfam PF00768), represented by E. coli PBP5, while PBPD3 is related to the VanY DD-carboxypeptidase family (Pfam PF02557). L. monocytogenes clinical isolates are resistant to cephalosporins but are, fortunately, susceptible to penicillin and ampicillin, which constitute the major treatment for listeriosis in combination with the aminoglycoside gentamicin.…”
Section: Cell Wall Metabolismmentioning
confidence: 99%
See 1 more Smart Citation